Degradation studies of amines and alkanolamines during sour gas treatment process - Islam, M.S.; Yusoff, R.; Ali, B.S.; Islam, M.N.; Chakrabarti, M.H. (International Journal of Physical Sciences, 2011)
Aqueous solutions of alkanolamines are widely used for the removal of acidic gases such as H 2S, CO 2, COS and CS 2 in the sour gas treatment process. In spite of the resistance of alkanolamines to chemical breakdown, plant and laboratory reports indicate that, on prolonged use, alkanolamines may be transformed into undesirable products from which the amines are not easily recovered. This phenomenon, commonly referred to as 'amine degradation', not only leads to amine losses, but may also contribute to operational problems such as foaming, corrosion, high solution viscosity and fouling as a result of decreasing the plant life. Amine based gas purification plants having absorption and stripping system, solvents are degraded at these two units mainly by oxidative degradation at absorber condition and thermal degradation at stripper condition. Identification of amine degradation routes, remediation of degradation, types of degradation products and studies on degradation reaction mechanism becomes essential for successful plant operation. Gas chromatography-mass spectrometry (GC-MS), ion chromatograph (IC), high performance liquid chromatography (HPLC), nuclear magnetic resonance spectroscopy (NMR) and Fourier transform infrared absorption spectrometry (FT-IR) are extensively used to identify the various degradation products. A comprehensive review of the latest research activities on alkanolamines degradation, best method for identification, various properties of degradation products and their classification is presented in this paper. This study would help to develop better understanding of amine degradation. Â© 2011 Academic Journals.